Selenomethionine Improves Mitochondrial Function by Upregulating Mitochondrial Selenoprotein in a Model of Alzheimer’s Disease - Chen, Chen; Chen, Yao; Zhang, Zhong-Hao; Jia, Shi-Zheng; Chen, Yu-Bin; Huang, Shao-Ling; Xu, Xin-Wen; Song, Guo-Li (Frontiers in Aging Neuroscience, 2021)
Alzheimer’s disease (AD), the most common neurodegenerative disease in elderly humans, is pathologically characterized by amyloid plaques and neurofibrillary tangles. Mitochondrial dysfunction that occurs in the early stages of AD, which includes dysfunction in mitochondrial generation and energy metabolism, is considered to be closely associated with AD pathology. Selenomethionine (Se-Met) has been reported to improve cognitive impairment and reduce amyloid plaques and neurofibrillary tangles in 3×Tg-AD mice. Whether Se-Met can regulate mitochondrial dysfunction in an AD model during this process remains unknown. In this study, the N2a-APP695-Swedish (N2aSW) cell and eight-month-old 3×Tg-AD mice were treated with Se-Met in vitro and in vivo. Our study showed that the numbers of mitochondria were increased after treatment with Se-Met. Se-Met treatment also significantly increased the levels of NRF1 and Mfn2, and decreased those of OPA1 and Drp1. In addition, the mitochondrial membrane potential was significantly increased, while the ROS levels and apoptosis rate were significantly decreased, in cells after treatment with Se-Met. The levels of ATP, complex Ⅳ, and Cyt c and the activity of complex V were all significantly increased. Furthermore, the expression level of SELENO O was increased after Se-Met treatment. Thus, Se-Met can maintain mitochondrial dynamic balance, promote mitochondrial fusion or division, restore mitochondrial membrane potential, promote mitochondrial energy metabolism, inhibit intracellular ROS generation and reduce apoptosis. These effects are most likely mediated via upregulation of SELENO O. In summary, Se-Met improves mitochondrial function by upregulating mitochondrial selenoprotein in these AD models.